Peningkatan Kapasitas Sumber Daya Manusia Dalam Optimalisasi Rekam Medis Elektronik Dan Dashboard Manajemen Untuk Mendukung Transformasi Digital Pelayanan - Diah Karlina (STIKES Columbia Asia Medan, 2026)
Digital transformation of hospital services requires health workers who are competent in operating Electronic Medical Records (EMR) and management dashboards. However, preliminary observation at RSU Mitra Sejati Medan indicated that the utilization of EMR and management dashboards had not been optimal because of the limited digital literacy of health workers and administrative staff. This community service program aimed to improve the capacity of hospital human resources in operating EMR, interpreting management dashboards, and supporting data-driven decision making. The program was conducted from March to June 2026, involving 40 participants consisting of unit heads, installation heads, supervisors, medical record officers, nurses, and administrative staff. The methods used were interactive lectures, workshops, simulations, case studies, hands-on practice, and three months of mentoring. Evaluation was carried out through pre-test, post-test, practical observation, and satisfaction questionnaire. The results showed that the average knowledge score increased from 58.6 to 84.9 (44.9% improvement), 92.5% of participants were able to operate basic EMR features, 87.5% were able to interpret management dashboards, and the satisfaction level reached 93.4%. This program contributed to strengthening digital health literacy and hospital readiness for digital transformation.